1989
DOI: 10.1161/01.res.65.5.1172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the characteristics of the flow velocity waveforms in left atrial small arteries and veins in the dog.

Abstract: To clarify the characteristics of the phasic blood velocity pattern in small arteries and veins on the left atrial surface, we used our newly developed fiber-optic laser Doppler velocimeter. We intended particularly to examine the Influence of atrial contraction and relaxation on velocity waveforms to obtain some insight into the nature of the mechanical force acting on the atrial intramyocardial vascular beds. In 14 anesthetized open-chest dogs, the left atrial appendage was gently displaced to expose small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Ashikawa et al (10) found that flow velocity in systole reverses in areas where the intramyocardial pressure is supposed to be negligible, the epicardial arteries and veins. Kajiya et al (36) found in small arterial vessels in the dog that flow velocity was not consistently linked to arterial pressure (their Figs. 6 and 9).…”
Section: Coronary Flow Impediment In Systolementioning
confidence: 99%
“…Ashikawa et al (10) found that flow velocity in systole reverses in areas where the intramyocardial pressure is supposed to be negligible, the epicardial arteries and veins. Kajiya et al (36) found in small arterial vessels in the dog that flow velocity was not consistently linked to arterial pressure (their Figs. 6 and 9).…”
Section: Coronary Flow Impediment In Systolementioning
confidence: 99%
“…We measured the blood velocity waveforms of LV by an optical fiber sensor of our laser Doppler velocimeter [23,26]. The fiber sensor was attached to a small vessel by cyanoacrylate so that the fiber sensor follows vascular motion on the beating canine heart.…”
Section: Introductionmentioning
confidence: 99%
“…In the phasic coronary blood flow pattern of the RCA, the systolic flow had the highest correlation with the transmural distribution of myocardial blood perfusion in the left atrium. Skalidis et al [7] and Kajiya et al [25] also reported a predominant systolic pattern of coronary arterial flow to the left atrium. The lower intraluminal pressure in the atrial artery and the thickness of the atrial wall contributes to the results.…”
Section: Discussionmentioning
confidence: 92%